Improving Access to Healthcare for Persons Living with Intellectual Disabilities: A Practical Guide for Policy Makers, Health Workers and Social Workers - Ofori-Dua, Kwadwo; Forkuor, John, Boulard; Dwumah, Peter; Dapaah, Jonathan, Mensah; Odongo, Douglas, Attoh (My University, 2022)
Across the globe, promoting the wellbeing of vulnerable populations is a key mandate of both governments and academics. Promoting the wellbeing of persons with intellectual disabilities is arguably one of the key responsibilities of social work academics in Ghana. In fulfilling this mandate, we have conducted a number of studies into the care and health needs of Persons Living with Intellectual Disabilities (PwIDs). We have prepared this policy brief as a way of informing policy and practice and making our research relevant to practitioners and policy makers in Ghana. Our aim is to, through this brief, bridge the divide between PwIDs and healthcare professionals.
Keywords: Access; Ghana; healthcare; persons with intellectual disabilities; policy makers; social workers